Study on the concrete quality analysis for water retaining structures in monaragala - Sabri, I.L.M. (University of Jaffna, 2018)
The concrete used for the structures for the storage of liquids where the exposure conditions for concrete are within the specified limits. Such structures include those retaining water or sewage, public swimming pools, etc. This concrete generally called as the concrete for water retaining structures. In order to construct durable and high quality concrete components, the transportation, placing and compacting of fresh concrete should be carried out with care, make sure that all the aspects regarding that can affect the quality of the concrete . In this study of “Study on the concrete quality analysis for water retaining structures in Monaragala”, the Kumbukkana water treatment plant under the Monaragala- Buttala integrated water supply project was selected. It is recently completed water supply project in Monaragala district. The scope of this study to analysis the quality of concrete for water retaining structures used in the Kumbukkana water treatment plant by used the statistical quality controlled charts and statistical tools by analysed tested sample results of fresh and hardened concrete. The concrete samples were prepared at the site and laboratory test were carried out at project laboratory. Statistically analysed the test results to quality analysis for concrete for water retaining structures by used statistical package Minitab 16 version. This study shows that based on the laboratory results and statistical analysis, According to National Water Supply and Drainage Boards “Specification for the Civil Engineering works” , mix design and statistical quality control technique Xbar Chart results, it can be conclude that the concrete for water retaining structure which tested samples were good in quality.
Keywords: Quality of concrete; Water retaining structures; Quality controlled charts; Xbar chart; Mix design